Transformasi Digital dalam Peningkatan Manajemen Aktivitas Panti Asuhan Al-Mabrur Bekasi Berbasis Sistem Informasi - Hendharsetiawan, Andy Achmad; Fitriyani, Aida; Khalida, Rakhmi; Sari, Rafika; Ramdhania, Khairunnisa Fadhilla (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
Information technology which continues to develop in various sectors of life requires the parties involved to be able to adapt to technology. Efforts to adapt technology are also continuing to be developed by the management of Al-Mabrur Orphanage Bekasi. A digital transformation carried out by the Al-Mabrur Orphanage in order to improve the management of student activities using an information system. Orphanages, as places for children who need protection and care, require an organized and efficient approach in monitoring and improving the quality of these children's daily lives. This training aims to provide understanding to orphanage managers and students regarding the use of information systems, to make it easier to record student participation in every activity held by the Al-Mabrur Orphanage. With an integrated information system, orphanages can create an environment that is more adaptive to technology and responsive to various activities in the orphanage. The output of this community service activity is that students can view and access activity data easily, and orphanage managers can have digital data recapitulation to monitor and evaluate student activities.